Implementasi Electronic Medical Record Di Rumah Sakit X Kabupaten Kudus - Ahmad Farid; Sela Maharani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study examines the implementation of an Electronic Medical Record (EMR) system at Hospital X in Kudus Regency and its impact on service efficiency, the quality of medical documentation, and regulatory compliance. A descriptive qualitative case study approach was used, involving eight key informants through interviews, direct observation, and document analysis. The findings reveal that EMR improves information accessibility, reduces recording errors, accelerates administrative processes, and enhances interdepartmental coordination. Key success factors include infrastructure readiness, continuous staff training, and managerial support. Challenges identified include limited skilled personnel, resistance to change, and high dependence on IT systems. A phased implementation, ongoing education, and technical assistance proved effective in facilitating digital transformation. The study concludes that EMR is a strategic component in developing a modern, integrated, and accountable healthcare system.